The Effect Of Spinning Wheel Media On Motivation To Learn Arabic For Grade IV Students MI Hidayatus Shibyan Cirebon - Afifah, Nur; Laily, Idah Faridah; Alfiani, Dwi Anita (UIN Siber Syekh Nurjati Cirebon, 2025)
This research is based on the low motivation and enthusiasm of students in participating in Arabic language learning. This study aims to determine the influence of spinning wheel media on students' motivation to learn Arabic. This type of research is quantitative research with experimental methods. The research design used is a pre-experimental one group pretest-posttest design. The population and sample from the study consisted of 32 students of MI Hidayatus Shibyan class IV. Data collection techniques use observation, questionnaires (warm). Data analysis used validity tests, reliability tests, normality tests, homogeneity tests, hypothesis tests, and n-gains. The results of the study showed that the use of Spinning Wheel learning media from the results of the observation sheets obtained was 100% with the category of very good. From the results of the questionnaire calculation on the motivation to learn Arabic, grade IV students obtained 85% results which were very strong. There is an influence of the use of Spinning Wheel learning media on the motivation to learn Arabic of fourth grade students of MI Hidayatus Shibyan, Cirebon Regency, this is seen from the results of the Paired T Test hypothesis test, which is 0.000 < 0.05 which means that Hα is accepted and H0 is rejected. It can be concluded that there is an influence between spinning wheel media on the learning motivation of fourth grade students of MI Hidayatus Shibyan, Cirebon Regency.Keywords: Spinning wheel, Motivation, Arabic Learn